Visual, Auditory, and Cross Modal Sensory Processing in Adults with Autism: An EEG Power and BOLD fMRI Investigation - Hames, Elizabeth’ C.; Murphy, Brandi; Rajmohan, Ravi; Anderson, Ronald C.; Baker, Mary; Zupancic, Stephen; O’Boyle, Michael; Richman, David (Frontiers in Human Neuroscience, 2016)
Electroencephalography (EEG) and Blood Oxygen Level Dependent Functional Magnetic Resonance Imagining (BOLD fMRI) assessed the neurocorrelates of sensory processing of visual and auditory stimuli in 11 adults with autism (ASD) and 10 neurotypical (NT) controls between the ages of 20-28. We hypothesized that ASD performance on combined audiovisual trials would be less accurate with observable decreased EEG power across frontal, temporal, and occipital channels and decreased BOLD fMRI activity in these same regions; reflecting deficits in key sensory processing areas. Analysis focused on EEG power, BOLD fMRI, and accuracy. Lower EEG beta power and lower left auditory cortex fMRI activity were seen in ASD compared to NT when they were presented with auditory stimuli as demonstrated by contrasting the activity from the second presentation of an auditory stimulus in an all auditory block versus the second presentation of a visual stimulus in an all visual block (AA2VV2). We conclude that in ASD, combined audiovisual processing is more similar than unimodal processing to NTs.